Birth context in the forties in a rural area of southern Spain - María de los Ángeles Castaño Molina; María Emilia Martínez Roche; Natalia Emilia Rodríguez Portilla; César Carrillo García (Universidad de Alicante, 2018)
In this study we set objectives to define the birth context of a rural town in Spain in the post-war period 1945-1950; to define what influence gender roles had on experience of these events; to identify what values and beliefs had influence on the childbirth process and to investigate which attitudes promoted change. Taking a qualitative approach, we chose an ethnographic method. The information was obtained through life story reports and semistructured interviews during 2009. The study was carried out in a rural town in southern Spain: Abarán, in the Region of Murcia. Eleven life stories were collected from women who became mothers between 1945 and 1950 and five semi-structured interviews were also carried out to enable triangulation and information expansion. After transcription of the interviews, the information was fragmented and, after thematic analysis of the content, three categories were defined: household work/economy, marriage/family and childbirth. Despite the way that gender roles defined the lives of men and women. Even though the social model of the time links women to activities at home, these women also worked hard at agricultural labour outside the home. The prevailing beliefs meant that many of the women were ignorant of their own bodies, even up until the moment of giving birth. Midwives were the reference professionals for this event.